Degradation of phenol using photocatalytic and biodegradation treatment of TIO₂/ZNO/N-mixed culture / Nur Syazrin Amalina Abdullah - Abdullah, Nur Syazrin Amalina (2018)
Harmful effect of industrial phenolic effluent which heavily toxified drinking water sources prompted scientist and environmentalists to look for ecologically favorable process of this recalcitrant substances. Phenols have been recognized as persistent and toxic pollutant leading to a significant threat to health problem and environmental consequently. The aims of this study were to investigate the possible removal treatments of phenol from synthetic wastewater using two treatment methods, namely photocatalysis and biological degradation. Mixed culture was used for the biodegradation of phenols, while in photocatalysis, dopant based TiC>2-visible light was used. The photocatalytic degradation of phenol was studied by a batch process using Ti02-ZnO and Ti02-ZnO-N as the catalyst on irradiation with visible light. The effect of process parameters such as pH, catalyst loading and initial concentration of phenol on the extent of degradation was investigated. The degradation of phenol was found to be effective in the acidic range. The optimum catalyst loading was observed at 3.0 g/L. The process followed the first order kinetics and the apparent rate constant decreased with increase in the initial concentration of phenol. FESEM, XRD, FTIR and BET were used to examine the characteristic of the materials applied. The better degradation of phenol was observed in the presence of doped Nitrogen photocatalyst as compared with undoped Nitrogen sample. Phenol biodegradation using acclimatized mixed culture was investigated in shake flask batch experiment. Prior to biodegradation, the mixed culture isolated from petrochemical wastewater effluent was acclimatized to a concentration of 50 mg/L of phenol over a period of four weeks. The process parameters namely pH, inoculums size, and initial phenol concentration were varied. A maximum degradation of 100% efficiency was achieved at 10 mg/L of initial phenol concentration, pH 7.0 and an inoculums size ofl0% (v/v) in biological part. The specific growth rate of the culture at various initial phenol concentrations were fitted to Monod models. It has been demonstrated that a sequential biological pretreatment followed by photocatalysis is able to enhance phenol degradation efficiency by 81%, which is 15% higher than the use of single treatment. It has also been pointed out that the photocatalytic pretreatment seem to have no significant impact by making phenol less biodegradable, as total gave essentially only about 68% degradation of phenol.